Department of Parasitology, Veterinary College, Navsari Agricultural University, Navsari. - Patil, AD; Lakde, CK; Sahatpure, AK; Chandni; Kamaljit (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
Excessive accumulation of fluid in arachnoid and /or in ventricular system of cranium lead to large size of cranium refers to hydrocephalus (Arthur et al., 2001). It is one of the rare congenital anomalies seen in cattle and buffalo while occasionally in ewe and doe (Dhaliwal et al., 1998). It may be caused due to abnormal development of fetus with genetic, nutritional and environmental factors (Kalman, 1989). An autosomal recessive gene is responsible for many hereditary cases but intrauterine infections and nutritional factor have not been fully evaluated except relationship of blue tounge virus with hydrocephaly (Upasana et al., 2012). Deficiency of Vitamin A may be a potent cause of hydrophalus in buffalo (Arthur et al., 2001).